Lipopolysaccharide Exposure Differentially Alters Plasma and Brain Inflammatory Markers in Adult Male and Female Rats - Hannah A. Nonoguchi; Timothy Wee Shang Kouo; Sandhya Kortagere; Joshua Hillman; David L. Boyle; Chitra D. Mandyam (Brain Sciences, 2022)
Humans and rodents have sexually dimorphic immune responses, which could influence the brain’s response to a systemic inflammatory insult. Lipopolysaccharide (LPS) is a stimulator of the innate immune system and is routinely used in animal models to study blood–brain barrier (BBB) dysfunction under inflammatory conditions. Therefore, we examined whether inflammatory response to LPS and the associated BBB disruption differed in male and female adult rats. Rats were treated with saline or two injections of 1 mg/kg LPS and studied 24 h after the second LPS injection. Plasma isolated from trunk blood and brain tissue homogenates of the prefrontal cortex (PFC), dorsal striatum (DS), hippocampus, and cerebellum were analyzed for cytokines and chemokines using a 9-plex panel from Meso Scale Discovery. BBB disruption was analyzed with tight junction proteins claudin-5 and VE-cadherin via Western blotting and VEGF by ELISA. This allowed us to compare sex differences in the levels of individual cytokines as well as associations among cytokines and expression of tight junction proteins between the plasma and specific brain regions. Higher levels of interferon-γ, interleukin-10 (IL-10), IL-13, IL-4, CXCL-1, and VEGF in the plasma were revealed compared to the brain homogenates, and higher levels of TNFα, IL-1β, IL-6, and IL-5 in the PFC were seen compared with plasma and other brain regions in males. Females showed higher levels of plasma CXCL1 and VEGF compared to males, and males showed higher levels of PFC TNFα, IL-6, IL-4, and VEGF compared to females. LPS induced significant increases in plasma cytokines and VEGF in both sexes. LPS did not significantly alter cytokines in brain tissue homogenates, however, it increased chemokines in the PFC, DS, and hippocampus. In the PFC, LPS produced BBB disruption, which is evident as reduced expression of claudin-5 in males and reduced expression of VE-cadherin in both sexes. Taken together, our results reveal significant sex differences in pro-inflammatory cytokine and chemokine levels in plasma and brain that were associated with BBB disruption after LPS, and validate the use of multiplex assay for plasma and brain tissue samples.